Few brief thoughts on the works of art stolen by the Nazis - Calvo Caravaca, Alfonso-Luis; Carrascosa González, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Cultural property litigation is often fascinating, creative, complex and full of all sorts of elements. Many of them take place before courts in the United States. One of the parties is usually a Jew or an heir to that Jew who was plundered from a work of art by the Nazis. 90 years have passed since National Socialism came to power in Germany (1933). However, these types of cases continue to occur. The purpose of this essay is to show the technical coordinates that explain the reasons why it is frequently litigated before US courts and the criteria used by them to determine which is the legal system applicable to the eventual restitution of the painting, the drawing, the score, sculpture, porcelain or any other similar object that is claimed.
Keywords: Stolen Art; good faith; blocked account; expropriation exception; nazi spoliation; replevin actions; Foreign Sovereign Immunities Act; the law of the State where the property is located at the time of the alleged transfer; repatriation of stolen Art, the most significant contact-Test; legal unilateralism